Combination of Modified Rhomboid Flap and Full-Thickness Skin Grafts (FTSG) for Scalp Defects Caused by Infiltrative Basal Cell Carcinoma (BCC): A Case Report - Komang Abdi Baskara Mayun; Hendry Irawan (Berkala Kedokteran, 2025)
Basal cell carcinoma (BCC) is the most common form of malignancy and its prevalence is increasing. BCCs have a low fatality rate but can cause severe morbidity, mainly through local damage. Full-thickness skin grafts (FTSGs) is a classic approach of reconstructing skin defects that have been utilised for wide defects. Objective of this study is to report an experience in treating BCC with wide excision and reconstruction using modified rhomboid flap and FTSG in Udayana University Hospital. A 75 years old female came with a complaint of lump in the head in the last 6 months ago. It was originally the size of a marble and progressively increasing. Physical examination showed a visible mass measuring 9x5 cm on the right temporoparietal region. The patient was diagnosed with BCC on the right temporoparietal region. It was planned for wide excision and reconstruction using modified rhomboid flap and FTSG. The donor site of the skin graft was harvested from the right inguinal. After underwent these procedures, a post-operative histopathological examination was conducted. The result showed BCC with infiltrative subtype. After one month, the reconstruction was acceptable and there was no sign of cancer recurrence. The flap and graft were in good and viable condition and there were no signs of inflammatory response. Combining modified rhomboid flap and FTSG gave numerous advantages for handling skin defects, especially in terms of healing process which shows better aesthetic and functional outcome, greater coverage, and less secondary contraction. These benefits can be seen in this case.